SYNTHESIS, CHARACTERIZATION AND BIOLOGICAL ACTIVITIES OF NOVEL MANNICH BASES DERIVED FROM ΒETA-NAPHTHOL - K.CHAKKARAVARTHI,; K.GOKULAKRISHNAN,; T.SUMAN,; D.TAMILVENDAN, (International Journal of Pharma and Bio Sciences, 2014)
This present study is concerned with the synthesis of novel β-naphthol Mannich bases with benzimidazole and p-toluidine by condensation reaction with appropriate aldehydes. The compounds 3-(phenyl(p-tolylamino)methyl) naphthalene-2-ol (TNPTB) and 3-((1H-benzo[d]imidazole-1-yl)methyl)naphthalene-2-ol (TNBIF) were synthesized and the chemical structures were characterized using spectral and analytical techniques. Mannich bases were screened for their antibacterial and antifungal activity against opportunistic bacterial and yeast pathogens. The antioxidant activity was tested using established methods. Among the tested ligands, TNBIF showed better antimicrobial and antioxidant activity compared to TNPTB.